2015
DOI: 10.1038/srep13127
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral shRNA against KCa3.1 inhibits allergic response in allergic rhinitis and suppresses mast cell activity via PI3K/AKT signaling pathway

Abstract: Calcium-activated potassium ion channel-3.1 (KCa3.1) plays a pivotal role in the potassium-calcium exchange involved in atopy. This study aimed to explore the impact of lentiviral-mediated shRNA silencing KCa3.1 on allergic response in a murine allergic rhinitis (AR) model. The BALB/c mice were divided into four groups: untreated AR group, negative control AR group, lentiviral KCa3.1-shRNA treated AR group and normal control group. Concentrations of ovalbumin (OVA)-specific IgE, histamine and leukotrienes C4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…It might be possible that the reduction of anion secretion also favour apical membrane hyperpolarization, a hypothesis that is supported by the more positive Vte recorded in the Kcnn4 -/-tissue that might be due to Na + accumulation in the mucosa and reduced anion secretion. Besides that, KCa3.1 inhibition has been widely proven by different groups to prevent or ameliorate several inflammatory events including those occurring in the airways (Girodet et al, 2013;Lin et al, 2015;Yu et al, 2017). Since our model is a systemic null-animal other might also participate in the reduction of inflammatory damage after Kcnn4 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…It might be possible that the reduction of anion secretion also favour apical membrane hyperpolarization, a hypothesis that is supported by the more positive Vte recorded in the Kcnn4 -/-tissue that might be due to Na + accumulation in the mucosa and reduced anion secretion. Besides that, KCa3.1 inhibition has been widely proven by different groups to prevent or ameliorate several inflammatory events including those occurring in the airways (Girodet et al, 2013;Lin et al, 2015;Yu et al, 2017). Since our model is a systemic null-animal other might also participate in the reduction of inflammatory damage after Kcnn4 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…As the PI3K conformation changes, Ser473 and Thr308 phosphorylation is required for Akt activation (21). A number of previous studies have demonstrated that the PI3K/Akt signaling pathway participated in the regulation of miRNAs on MC degranulation (22)(23)(24). miR-155 controlled MC activation by modulating the PI3KÎł signaling pathway and anaphylaxis in mice with cutaneous anaphylaxis (22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-8 expression has been shown to be regulated by the PI3K/AKT signaling pathway [65]. The PI3K/AKT signaling pathway also plays a key role in the IgE-mediated maturation and activation of mast cells [66,67]. The suppression of the PI3K/AKT signaling pathway has been reported to lead to the inhibition of TNF-α-induced inflammation [68].…”
Section: Discussionmentioning
confidence: 99%